Developing a pre-competition anxiety scale for football players in the premier clubs of the Kurdistan Region - Iraq - Mahmoud, Niaz Ali; Asaad, Asst. Prof .Dr. Diyar Kamal (Sulaimani Journal for Humanities, 2026)
The research aims to build a pre-competition anxiety scale for football players in Iraqi clubs. The research population was identified as football players in the Kurdistan Region of Iraq, numbering (286) players, including (175) players as the construction sample, after excluding those who participated in the exploratory experiment, numbering (30) players. The researchers used the descriptive approach with a survey method, and the researchers reached a number of conclusions and recommendations.